ChemInform Abstract: A New Convenient Synthetic Approach to Diarylpyrimidines. Issue 43 (7th October 2016) - Guirado, Antonio; Alarcon, Enrique; Vicente, Yesica; Andreu, Raquel; Bautista, Delia; Galvez, Jesus
Abstract: Two pathways to the desired compounds are presented: a stepwise and a one‐pot procedure which both are operationally simple.